Effectiveness of a mindfulness-based program with virtual reality to increase safe behaviors in workers of a mining company - Guzmán, Raúl; Chávez-Luque, Yuri Félix; Guzmán, Nisida; Medina, Guillermo Sebastián; Valdiviezo, Celin Daniel; Santa-Cruz, Alejandro (Frontiers in Psychology, 2025)
ObjectivesThe development of safe behaviors is a transcendental issue, especially in organizations where jobs considered high risk, such as mining, are carried out. This study proposes a program aimed at increasing safe behavior through a mindfulness program supported by virtual reality techniques. The specific objective was to determine the effect of this program on safe behaviors, comparing with those produced with the BBS (Safety Based On Behavior) program in a sample of workers who performed high-risk activities in a mining company in southern Peru.MethodBased on the determination of high-risk activities for the study, the study groups were randomly selected, forming two equivalent groups in terms of sex, age, education, and marital status. The study units were randomly assigned to one of the following 2 groups: 22 to the control group (BBS) and 22 to the experimental group (mindfulness) to whom record sheets of safe behaviors related to standard risk behaviors were applied for each activity on a weekly basis, according to the BBS system where the observers did not know the composition of the groups under study.ResultsData analysis showed evidence of a significant improvement in the index of safe behavior thanks to the proposed mindfulness program, compared to the BBS program alone.ConclusionEvidence was found that the mindfulness-based program significantly reduces the number of risk behaviors likely to cause workplace accidents, maintaining that mindfulness is a very useful tool to reduce the number of incidents and/or accidents in workers. An organization, in this case, a mining company.